2016
DOI: 10.5500/wjt.v6.i1.239
|View full text |Cite
|
Sign up to set email alerts
|

Singlevsdual (en bloc) kidney transplants from donors ≤ 5 years of age: A single center experience

Abstract: AIM:To compare outcomes between single and dual en bloc (EB) kidney transplants (KT) from small pediatric donors. METHODS:Monocentric nonprospective review of KTs from pediatric donors ≤ 5 years of age. Dual EB KT was defined as keeping both donor kidneys attached to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
(50 reference statements)
1
19
0
Order By: Relevance
“…EB transplantation facilitates the completion of the vascular anastomoses compared to SK transplants from small pediatric donors . Transplanting a SK from a small pediatric donor anastomoses small donor vessels to small recipient vessels, in relatively hypotensive patients (compared to adult recipients), which may result in early technical failure . In the United States, approximately 3% of pediatric first‐time renal transplant recipients are already sensitized with PRA >80%, due to prior exposure to blood transfusions or other organ transplants.…”
Section: Discussionmentioning
confidence: 99%
“…EB transplantation facilitates the completion of the vascular anastomoses compared to SK transplants from small pediatric donors . Transplanting a SK from a small pediatric donor anastomoses small donor vessels to small recipient vessels, in relatively hypotensive patients (compared to adult recipients), which may result in early technical failure . In the United States, approximately 3% of pediatric first‐time renal transplant recipients are already sensitized with PRA >80%, due to prior exposure to blood transfusions or other organ transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Bhayana et al 9 described that 5-year survival in adult recipients of kidneys from 0- to 5-year-old donors was comparable between en bloc and single-kidney transplants; however, 10-year graft survival was better with en bloc than with single-kidney transplants. Al-Shraideh et al 11 reported that 60-month graft survival was better with en bloc than with single-kidney transplants in adults receiving kidneys from 5-year-old or younger donors.…”
Section: Discussionmentioning
confidence: 99%
“…4-11 In terms of size-mismatch kidney transplantation from very young and small donors to adult recipients, some studies have recommended that the choice between en bloc and single-kidney transplantation be based on donor age, 24-26 donor weight, 10 or relative size of the donor and recipient. 27,28 Hidden behind the age-based recommendations may be the podocyte maturational level of donor kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aforementioned study of Kayler et al, they reported that the outcomes of SKT of donor 10‐34 kg are similar to non‐ideal standard deceased donor and underlined that SKT provides more cumulative graft years. Mohanka et al showed that there is no difference in 1‐year graft survival between SKT and EBKT for donor less than 15 kg in adult recipients (79% vs 86%, P = 1.000), and Al‐Shraideh et al reported similar results for donor younger than 5 years 16,17 . In pediatric recipients, Sui et al compared the outcomes of SKT with donors 5‐15 kg and EBKT with donors 2.5‐5 kg 18 .…”
Section: Discussionmentioning
confidence: 99%